ON QUASI-HOLOMORPHIC DIFFERENTIAL-EQUATIONS - Moroz, I (1990)
Complexifications of some codimension-one normal forms are investigated and are shown to support Hopf bifurcations with limit cycles existing only at the bifurcation points. The behaviour of such equations is relevant to telecommunication systems. © 1990.